THE USE OF A CROCKMETER MACHINE FOR RUBBING TEST ON PARCHMENT SKIN - Muhammad Ikhwan (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2022)
One of the small industries that survives and needs to be developed is the shadow puppet industry. The shadow puppet industry uses parchment skin as the main raw material. As a laboratory institution, the author tested the quality of parchment skin dye paint for shadow puppet using a crockmeter machine. The test is carried out by adding an auxiliary material in the form of ethylene glycol to the dye paint which is expected to improve the quality of the rubbing resistance of the dye paint on the shadow puppets. In this test the author uses parchment skin from sun-dried buffalo skin with a transparent color and an even thickness of the skin and a large cross-sectional area so that no part is wasted. Furthermore, the parchment skin surface was sanded before staining. This sanding aims to level the parchment skin surface and remove the remaining collagen, protein and fat. The test was carried out using 3 samples. Sample I used coloring materials (mowilex paint, foxputih glue, water and finishing using mowilex clear). Sample II uses coloring materials (mowilex paint, white fox glue, water, Ethylen Glycol and finishing using mowilex clear). Sample III uses dyes (mowilex paint, white fox glue, water, Ethylen Glycol, finishing using mowilex clear and the addition of a clearing process using a sunlight wetting agent. From the experiments and tests carried out, better results were obtained for the use of Ethylen Glycol in the coloring and also the clearing process to improve the color quality of the wayang kulit products produced.